Algunas evidencias de las interacciones entre los recuay y la costa norte durante los períodos Intermedio Temprano y Horizonte Medio - Ibarra Asencios, Bebel (2025)
This report presents the results of the research undertaken at Huamparán, a site in the Conchucos Region associated with the Recuay culture. Two uncommon ceramic vessels found during excavations are herein described and their origin is discussed. These objects are the first evidence of the interaction between the North Coast (possibly the Gallinazo or the Moche) and the eastern highlands of Ancash at the beginning of the Middle Horizon (c. 500-700 A.D.). Although the nature of these interactions has yet to be established, we posit that in this region the Recuay took part in long-distance exchanges without any influence of the Wari State.